2020
DOI: 10.1097/sla.0000000000004116
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Elective Major Cancer Surgery During COVID 19 at Tata Memorial Centre

Abstract: Background: Overburdened systems and concerns of adverse outcomes have resulted in deferred cancer surgeries with devastating consequences. In this COVID pandemic, the decision to continue elective cancer surgeries, and their subsequent outcomes, are sparsely reported from hotspots. Methods: A prospective database of the Department of Surgical Oncology was analysed from March 23rd to April 30th, 2020. Findings: Four hundred ninety-four elective surgeries were performed (377 untested and 117 tested for Covid 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
62
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 7 publications
11
62
0
1
Order By: Relevance
“…The low rates of major complications in our series reflect appropriate case selection and early adoption's best surgical practices and stringent standard operating procedures. Our surgical outcome experience is in concordance as reported by Shrikhande et al [15].…”
Section: Discussionsupporting
confidence: 92%
“…The low rates of major complications in our series reflect appropriate case selection and early adoption's best surgical practices and stringent standard operating procedures. Our surgical outcome experience is in concordance as reported by Shrikhande et al [15].…”
Section: Discussionsupporting
confidence: 92%
“…With adequate preparedness, we were able to perform close to five hundred major cancer surgeries between 23rd March 2020, and 30th April 2020 with no worsening of perioperative outcomes. 15 During the initial days of the pandemic, we did not adopt Similar to some of the findings in the present study, Benitez et al reported that more than half of the respondents in their study reported that the use of PPE affected surgical performance. They also reported visibility impairment due to goggle fogging by two-thirds of the respondents.…”
Section: Discussionsupporting
confidence: 60%
“…Use of high-efficiency particulate air filters, low intra-abdominal pressures during surgery, minimal usage of energy devices, small port sizes, and evacuation of gases before the extraction of the specimen have been recommended. 24 This concern was seen across all the oncosurgeons in our study with a decrease in MIS cases in agreement with the results of Shrikhande et al 23 Telemedicine options are being explored by many hospitals to maintain the continuum of care, especially for oncologic surveillance.…”
Section: Discussionsupporting
confidence: 91%
“…Breast, HN, gynecology, and colorectal oncology formed the major chunk of oncologic work in India, in agreement with the results of Shrikhande et al 23 Major surgeries in HPB, CRS/HIPEC, and thoracic oncology are resource-intense procedures with perspectives of PPE use, critical care support, and blood blank supplies, hence we observed that oncosurgeons were reluctant to operate such cases.…”
Section: Discussionsupporting
confidence: 90%